ಗುಮಟ್ - Gopal Gowdam, M. (Karnataka Konkani Sahitya Academy, 2011)
This books gives more information on Traditional Folklore Percussion of an Instrument and authentic presentation of History, its cultural importance and use in various ethnic groups in india
Gumat
Keywords: Konkani; Folklore Instrument; Konkani; Konkani